Strategi Penyiaran Radio Mustang 88 FM dalam Mempertahankan Pendengar (Studi Kasus Program Mustang Morning Squad) - Manuella, Febryna Glory; Rusdi, Farid (Koneksi, 2022)
The mass media in Indonesia have difficulty maintaining their existence during the pandemic. The media face challenges, go bankrupt or survive. Radio, as one of the mass media, is a medium that is less accessible to the audience because the information is presented in audio form, not audiovisual like television. However, radio still survives in the digital era and even more so during the COVID-19 pandemic. Through this article, the author presents research on one of the radio stations in Indonesia, namely Radio Mustang 88 FM, through the Mustang Morning Squad program. Radio Mustang 88 FM implements a broadcasting strategy to maintain its existence. The Mustang Morning Squad program has a unique characteristic compared to other programs. The author uses the concept of mass communication, DeFleur's communication model, and customer engagement to reveal the broadcasting strategy implemented to retain listeners amid a crisis. This study uses a qualitative method. Data were collected by observing the Mustang Morning Squad broadcasting process and interviews. The results show that updating information related to daily life will increase customer engagement. Communication between teams also plays an important role. Media massa di Indonesia memiliki kesulitan untuk mempertahankan eksistensinya selama masa pandemi. Media menghadapi tantangan, bangkrut atau bertahan. Dari berbagai media massa, radio adalah media yang kurang dijangkau oleh khalayak karena informasi disajikan dalam bentuk audio, bukan audiovisual sepertihalnya televisi. Namun demikian, radio masih tetap bertahan di era digital dan terlebih lagi pada masa pandemi covid-19. Melalui artikel ini, penulis menyajikan penelitian pada salah satu radio di Indonesia yaitu Radio Mustang 88 FM melalui program Mustang Morning Squad. Radio Mustang 88 FM menerapkan strategi penyiaran untuk mempertahankan esksitensinya. Program Mustang Morning Squad memiliki ciri khas yang unik dibanding program lain. Penulis menggunakan konsep komunikasi massa, model komunikasi DeFleur, dan keterlibatan pelanggan untuk mengungkap strategi penyiaran yang diterapkan dalam mempertahankan pendengar di tengah kondisi krisis. Penelitian ini menggunakan metode kualitatif. Pengumpulan data dilakukan dengan cara observasi pada proses penyiaran Mustang Morning Squad, dan wawancara. Hasil penelitian menunjukkan bahwa memperbarui informasi terkait dengan kehidupan sehari-hari akan meningkatkan keterlibatan pelanggan. Komunikasi antar tim juga memegang peran penting.